Development of an MTF in ADINA and its application to the study of the Yuxi Basin effect - Li, Tiefei; Chen, Xueliang; Li, Zongchao (Journal of seismology, 2021)
A three-dimensional multitransmitting formula is developed in ADINA to simulate the input of seismic waves and the scattering of infinite domains at the same time, consistent with the progress of the explicit finite element method of lumped mass. A three-dimensional cube model is built, and a delta pulse wave is input to compare the simulation results with the analytical solutions. The simulation results show that the peak error is 0.2% of the input wave, which meets the requirements of the usual numerical simulation. This method has a certain efficiency advantage in site effect analyses of fine models for localized fields. A velocity structure model of the Yuxi Basin is built, and the associated basin effect is studied by numerical simulation. The distribution of the focusing effect is related to the structure of the narrow east-west and wide north-south features in the Yuxi Basin, and the edge effect is related to the slope of the basin base. A distribution map is given of the amplification effect of ground motion in the basin.